Development and diseases of the coronary microvasculature and its communication with the myocardium - Neffeová, Kristýna; Olejníčková, Veronika; Naňka, Ondřej; Kolesová, Hana (WIREs mechanisms of disease, 2022)
We review the current understanding of formation and development of the coronary microvasculature which supplies oxygen and nutrients to the heart myocardium and removes waste. We emphasize the close relationship, mutual development, and communication between microvasculature endothelial cells and surrounding cardiomyocytes. The first part of the review is focused on formation of microvasculature during embryonic development. We summarize knowledge about establishing the heart microvasculature density based on diffusion distance. Then signaling mechanisms which are involved in forming the microvasculature are discussed. This includes details of cardiomyocyte-endothelial cell interactions involving hypoxia, VEGF, NOTCH, angiopoietin, PDGF, and other signaling factors. The microvasculature is understudied due to difficulties in its visualization. Therefore, currently available imaging methods to delineate the coronary microvasculature in development and in adults are discussed. The second part of the review is dedicated to the importance of the coronary vasculature in disease. Coronary microvasculature pathologies are present in many congenital heart diseases (CHD), especially in pulmonary atresia, and worsen outcomes. In CHDs, where the development of the myocardium is impaired, microvasculature is also affected. In adult patients coronary microvascular disease is one of the main causes of sudden cardiac death, especially in women. Coronary microvasculature pathologies affect myocardial ischemia and vice versa; myocardial pathologies such as cardiomyopathies are closely connected with coronary microvasculature dysfunction. Microvasculature inflammation also worsens the outcomes of COVID-19 disease. Our review stresses the importance of coronary microvasculature and provides an overview of its formation and signaling mechanisms and the importance of coronary vasculature pathologies in CHDs and adult diseases. This article is categorized under: Cardiovascular Diseases > Stem Cells and Development Congenital Diseases > Molecular and Cellular Physiology Cardiovascular Diseases > Molecular and Cellular Physiology.
Keywords: kardiovaskulární nemoci; Humans; heart development; kardiomyocyty; Female; myocardium; dospělí; coronary vessels; lidé; Myocytes, Cardiac; Microvessels; Adult; COVID-19; ženské pohlaví; Cardiovascular Diseases; Endothelial Cells; mikrocévy; endoteliální buňky; myokard; Myocardium; pulmonary atresia; coronary microvasculature